PENGARUH AROMATERAPI LAVENDER TERHADAP KECEMASAN IBU BERSALIN PADA PANDEMI COVID-19 DI PUSKESMAS I DENPASAR TIMUR - Ni Wayan Noviani; Ni Luh Putu Citrawati; Putu Savitri Astikasari (JOMIS (Journal of Midwifery Science), 2022)
Non-natural disasters caused by the Covid 19 virus that is currently engulfing Indonesia is currently one of the factors that can cause anxiety in mothers who will face childbirth. Anxiety in childbirth is a common condition for pregnant women. Mothers who experience anxiety in the labor process can cause pathological conditions. An alternative treatment to reduce anxiety in maternity mothers is to use aromatherapy. The results of this study aim to find out the effect of lavender aromatherapy on the anxiety of maternity mothers in the covid-19 pandemic. This type of research is a quasi experiment with one group pretest-posttes without control. The population in this study was all mothers who were pregnant in the working area of Puskesmaa I Denpasar Timur with a sample of 20 maternity mothers who fit the criteria of inclusion and taken purposive sampling. The data collection tool used is a DASS questionnaire. The results of this study using a paired t-test showed that there was a meaningful difference between the level of anxiety before being given aromatherapy and after being given aromatherapy judging from the p-value of < 0.05.